Paediatric forearm fractures. Issue 5 (October 2018) - Widnall, James; Bruce, Colin
Abstract: Paediatric forearm fractures are a common presentation to orthopaedic surgeons. They include a number of different injuries including diaphyseal fractures, distal radius fractures and Galeazzi equivalent injuries. Apart from angulation, there is often a rotational component to the injury that must be assessed and accounted for to allow adequate reduction. The majority can be treated via conservative methods however K-wire fixation, plating and more recently elastic nails have all been utilised to good effect. K-wires can be used in a trans-physeal fashion or via an intrafocal technique. Outcomes between plate and nail fixation appear similar but nails offer better cosmesis and easier hardware removal. There has been a recent trend towards non-operative treatment of grade 1 open injuries of the forearm but this is yet to have the backing of level I evidence.